Removal of pollutants from disperse black dye wastewater by mucilage from dragon fruit peel - Van, Doan Thi; Quang, Pham Van; Anh, Ngo Van; Huan, Nguyen Huu; Oanh, Le Thi Hoang (Vietnam Journal of Science and Technology, 2020)
Apart from the large revenue, the textile industry in general and the dyeing process in particular are releasing huge amounts of wastewater that pollutes the environment and adversely affects human health. Treatment of this type of wastewater by coagulation and flocculation process requires lots of synthetic chemicals, implying a chemical hazard. Thus, this study evaluated the efficacy of mucilage extracted from the peel of dragon fruit (Hylocereus undatus) towards partly substitution of Poly Aluminium Chloride (PAC) used in coagulation and flocculation process for removal of turbidity and other pollutants from disperse black dye wastewater. The effects of pH, settling time, coagulant dosage and mucilage dosage on removal of turbidity, chemical oxygen demand (COD) and color, etc. were analyzed based on Jar-tests. The results showed that the addition of mucilage at 10 mg/L after PAC at 245 mg/L under optimal pH 7 and settling time 40 minutes removed turbidity up to 94.92%. The amount of PAC used was 3-10% less compared to total PAC needed for obtaining equal efficiency when used alone. The pollutant removal by mucilage was also comparable to Polyacrylamide (PAM) – a synthetically organic flocculants.